Risk Stratification by Cross-Classification of Central and Brachial Systolic Blood Pressure - Cheng, Yi-Bang; Thijs, Lutgarde; Aparicio, Lucas S; Huang, Qi-Fang; Wei, Fang-Fei; Yu, Yu-Ling; Barochiner, Jessica; Sheng, Chang-Sheng; Yang, Wen-Yi; Niiranen, Teemu J; Boggia, José; Zhang, Zhen-Yu; et al. (Hypertension (Dallas, Tex., 2022)
BACKGROUND: Whether cardiovascular risk is more tightly associated with central (cSBP) than brachial (bSBP) systolic pressure remains debated, because of their close correlation and uncertain thresholds to differentiate cSBP into normotension versus hypertension. METHODS: In a person-level meta-analysis of the International Database of Central Arterial Properties for Risk Stratification (n=5576; 54.1% women; mean age 54.2 years), outcome-driven thresholds for cSBP were determined and whether the cross-classification of cSBP and bSBP improved risk stratification was explored. cSBP was tonometrically estimated from the radial pulse wave using SphygmoCor software. RESULTS: Over 4.1 years (median), 255 composite cardiovascular end points occurred. In multivariable bootstrapped analyses, cSBP thresholds (in mm Hg) of 110.5 (95% CI, 109.1-111.8), 120.2 (119.4-121.0), 130.0 (129.6-130.3), and 149.5 (148.4-150.5) generated 5-year cardiovascular risks equivalent to the American College of Cardiology/American Heart Association bSBP thresholds of 120, 130, 140, and 160. Applying 120/130 mm Hg as cSBP/bSBP thresholds delineated concordant central and brachial normotension (43.1%) and hypertension (48.2%) versus isolated brachial hypertension (5.0%) and isolated central hypertension (3.7%). With concordant normotension as reference, the multivariable hazard ratios for the cardiovascular end point were 1.30 (95% CI, 0.58-2.94) for isolated brachial hypertension, 2.28 (1.21-4.30) for isolated central hypertension, and 2.02 (1.41-2.91) for concordant hypertension. The increased cardiovascular risk associated with isolated central and concordant hypertension was paralleled by cerebrovascular end points with hazard ratios of 3.71 (1.37-10.06) and 2.60 (1.35-5.00), respectively. CONCLUSIONS: Irrespective of the brachial blood pressure status, central hypertension increased cardiovascular and cerebrovascular risk indicating the importance of controlling central hypertension.
Keywords: hypertension; central blood pressure; Humans; Risk Assessment; cardiovascular risk; lidé středního věku; Middle Aged; Hypertension; měření krevního tlaku; arteria brachialis; mortality; Blood Pressure; Brachial Artery; brachial blood pressure; mužské pohlaví; krevní tlak; population science; Blood Pressure Determination; ženské pohlaví; hodnocení rizik; hypertenze; lidé; Male; Female